READING BEHAVIOR IN ACADEMIA: DOES SMARTPHONE OVERUSE MATTER? (IJOVTECH, 2026)
Reading is an essential skill that should be developed in any culture and an integral part of the educational infrastructure of any society. On the other hand, reading habits in Nigeria are hindered by several factors, such as mobile devices' rapidly advancing technological capabilities. The present study examined over-dependency on smartphones as a potential variable that could account for the variations in reading behavior among students. Two hundred and fifty-two undergraduates enrolled in three public higher education institutions in Ebonyi State participated in the survey. The respondents completed a self-report measure of the Smartphone Addiction Scale-Short Version (SAS-SV) and Reading Behavior Scale. The simple regression analysis performed on the data revealed that smartphone overuse statistically significantly correlated with the student's reading behaviorβ = .66. The findings suggest that the hypothesis that the prevalence of smartphone overuse would significantly predict reading behavior among students was correct and warranted more investigation. The practical implications and recommendations are discussed.